Bifidobacterium animalis subsp. lactis A6 alleviates perennial allergic rhinitis in adults by inhibiting serum total IgE and IL‐13: A randomized, double‐blind, placebo‐controlled trial - Langrun Wang; Shiwen Zhou; Huiyu Chen; Chao Zhang; Meiwen Sun; Qi Zhang; Yinghua Liu; Shaoqi Shi; Shaoyang Ge; Juan Chen; Yanling Hao; Yong Zhang; et al. (Clinical and Translational Allergy, 2025)
Abstract Objectives The evidence regarding the efficacy of probiotics in improving allergic rhinitis (AR) remains inconsistent. This study aimed to evaluate the potential effects of Bifidobacterium animalis subsp. lactis A6 (A6) on perennial AR. Methods A randomized, double‐blind, placebo‐controlled trial was conducted involving 70 adults with perennial AR receiving either probiotic (A6, 5 × 1010 CFU/sachet per day) or placebo intervention for 8 weeks. Nasal symptoms and quality of life (QoL) were recorded using total nasal symptom scores (TNSS) and the rhinitis quality of life questionnaire (RQLQ). Blood eosinophil count, total immunoglobulin E (IgE), allergen‐specific IgE, and immunological parameters were also assessed. Results After 8 weeks of intervention, the probiotic group showed a statistically significant greater reduction in TNSS total score compared with the placebo group [−3.11 (3.53) vs. −1.29 (3.34), p = 0.029, Cohen's d = 0.68]. Similar results were noted for serum total IgE and interleukin‐13 (IL‐13). Comparable findings were seen for RQLQ score only at week 4 but not at week 8. Conclusions In conclusion, A6 could statistically significantly alleviate rhinitis symptoms and improve QoL in adults with perennial AR. The effect size, as measured by Cohen's d, suggests that A6 may provide clinically meaningful benefits for AR patients to a certain degree. Clinical Trial Registration Chictr.org.cn Identifier no. ChiCTR2200064158.